ANALISIS WACANA CITRA I KETUT SUDIKERTA DI FACEBOOK PERIODE JANUARI – DESEMBER 2017 - Narayani Murti, Dewa Ayu Putu Jiyestha; Gelgel, Ni Made Ras Amanda; Pradipta, Ade Devia (E-Jurnal Medium, 2018)
ABSTRACT An image is very important for a politician to attain the attention from the society. Politician’s image need to be built and maintained in order to attain sympathy from the public. The process of building an image requires the media to share the informations. They have their own way to show the particular image, in order to attain more supports from the society. The using of social media of this purpose is such a requirement to reach the bigger range of society in order to influence them. Many politicians using Facebook to keep on communicating with their constituents. One of these politicians is I Ketut Sudikerta, who used to maintain this kind of social media to achieve the society’s empathy. He updates his Facebook timeline by uploading his daily activities photos. To observe the politician’s image on social media, we can use text analysis technic, to comprehend the intention of social media utilization on politic. The research aim at explaining text analysis of the image of I Ketut Sudikerta on Facebook on January until December 2017. This research using qualitative approach with Van Dijk analysis. The result of this research found that, there are 5 categories of image have been established: hardworking politician, down to earth, simple, local genius, young spirited, dynamic. Keyword: Facebook, I Ketut Sudikerta, Image, Text Analysis, Van Dijk